USE OF KRYVYI RIH MINING AND INDUSTRIAL LANDSCAPES FOR VARIOUS TYPES OF SPORTS TOURISM - Шиян, Дарія; Лакомова, Олена; Карпенко, Тетяна; Сопов, Дмитро (SWorldJournal, 2022)
Sports tourism is one of the areas of active recreational activities in the structure of mass leisure development. Ensuring sports tourism requires finding and substantiating new areas for hiking routes, expanding the training base with new suitable faci